Durability Study of Basalt Fiber-reinforced Bars Exposed to Harsh Environments - Alrifai, Mohamad Mazen (2019)
A Master of Science thesis in Civil Engineering by Mohamad Mazen Alrifai entitled, “Durability Study of Basalt Fiber-reinforced Bars Exposed to Harsh Environments”, submitted in April 2019. Thesis advisor is Dr. Farid Abed and thesis co-advisor is Dr. Tamer El Maaddawy. Soft and hard copy available.